The reason for the preferential use of finger millet (Eleusine coracana) in eastern African brewing. Issue 1 (21st January 2016) - Kubo, Ryosuke
Abstract : Finger millet ( Eleusine coracana ) is a cereal that is widely used as an ingredient for alcoholic beverages in Eastern Africa. However, the reason for its preferred use in brewing over other types of cereal is still unknown. In this study, we aim to clarify the reason for selective use of finger millet in Eastern African brewing, through a field survey and laboratory experiments. The field survey was conducted in a rural village of Tanzania, named Bupigu. In the village, finger millet was used to prepare four types of foods: ugali (stiff porridge), uji (thin porridge), togwa (saccharified beverage) and pombe (alcoholic beverage). Among them, pombe brewing was the principal method of utilization. In addition, the survey showed that the villagers recognize that finger millet is responsible for the strong taste of pombe . Furthermore, the laboratory experiment showed that the α ‐amylase activity of finger millet is higher than that of other cereals cultivated in Eastern Africa, suggesting that finger millet is a preferable ingredient for enhancing the efficiency of ethanol production. In conclusion, this study demonstrated that the high amylase activity, which led to high ethanol concentrations in the alcoholic beverages, is a preferable characteristic of the finger millet.